(The Improvement of Hot Oil Immersion Drying (HOID) Method in Coconut Oil Production) - Dadang Supriatna; Yang Yang Setiawan (Balai Besar Industri Agro, 2000)
Hot oil immersion drying (HOID) of fry dry technology is a method of coconut oil extraction that involves drying the grated coconut kernel by immersion in hot coconut oil and then expelling the oil from the cooked pieces. the technology used was the secound generation, which has been improved from the frist one. the coconut oil can be used as cooking oil without any chemical purification and also to be used in cosmetic and pharmaceutical manufacturing. observation was done on processing technology and techno-economical study. the result showed that the improved technology was more efficient then the frist one and is able to reduce the oil spilled out of the pans which happened in the first generation technology. the coconut oil produced met the FFA and moinsature content requirements of indonesian industrial standard of cooking oil. base on the financial analtysis, conducting this technology commercially at 2000 nuts/day capacity was feasible which will give the internal rate of return (IRR) value at 22.38% and pay back period (PBP) 4.5 years. adding on initial investment of second-generation technology was not influencing the feasibility of the operational.